2019
DOI: 10.5562/cca3543
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy as a Tool for Studying Asphaltene Composition

Abstract: Asphaltenes are the most polar oil components with molecular weights between 500 and 1000 Da, which primarily consist of carbons and hydrogens, some heteroatoms, such as nitrogen, sulphur, oxygen and traces of nickel, vanadium and iron. Owing to their extreme complexity, it is almost impossible to completely identify all the compounds present in asphaltene samples. Various analytical techniques and approaches were used to characterize asphaltenes but their structure and composition are still a matter of thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It can be seen from Table 3 that the values of aromatic rates f A of the pristine asphaltene, MeOHS, and MeOHI were 0.64, 0.42, and 0.70, respectively. The value of aromatic rate f A of the MeOHS was smaller than that of the pristine asphaltene, indicating that the proportion of aromatic carbon in the MeOHS was small [ 45 , 46 , 47 ]. In contrast, the aromatic rate f A of MeOHI was larger than that of pristine asphaltene, indicating that aromatic carbon accounted for a large proportion of MeOHI.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen from Table 3 that the values of aromatic rates f A of the pristine asphaltene, MeOHS, and MeOHI were 0.64, 0.42, and 0.70, respectively. The value of aromatic rate f A of the MeOHS was smaller than that of the pristine asphaltene, indicating that the proportion of aromatic carbon in the MeOHS was small [ 45 , 46 , 47 ]. In contrast, the aromatic rate f A of MeOHI was larger than that of pristine asphaltene, indicating that aromatic carbon accounted for a large proportion of MeOHI.…”
Section: Resultsmentioning
confidence: 99%
“…F I G U R E 2 Typical 1 H and 13 C NMR spectra of asphaltenes recorded in CDCl 3 . Reproduced from Vukovi c et al 17 for evaluating the molecular weight properties of asphaltenes and not the result of artifacts such as fragmentation, polymerization, and incomplete volatilization, which may be occurring during the simple MS and NMR experiments.…”
Section: General Overviewmentioning
confidence: 99%
“…Owing to the complexity of asphaltene composition, 1 H and 13 C NMR spectra consist of a number of overlapping signals assigned to different hydrocarbon types. Comprehensive studies of asphaltenes by means of 1 H and 13 C NMR over the past several decades have revealed characteristic functional groups of asphaltenes and the spectral regions in which their protons resonate, 17 as shown in Figure 2. Quantitative 13 C NMR spectra characterize the aromatic and saturated carbon contents of asphaltenes.…”
Section: Nmr Of Asphaltenesmentioning
confidence: 99%
See 1 more Smart Citation